PERSONAL SELLING CROWN GROUP AUSTRALIA KEPADA CALON PEMBELI DI INDONESIA - Gracia Rachmi Adiarsi; Clara Olivia (Avant Garde, 2017)
Personal selling is important for marketing communication in order toconnect directly with the prospective buyers. The purpose of this research is toanalyze the process of personal selling and the elements of Crown Group sales teamas communicator in order to persuade the prospective buyers. This research usedqualitative methodology, personal selling and persuasive communication. The resultof this research found that the use of personal selling through the sales person andthe sales team elements as a communicator could be one of the ways to persuade theprospective buyers of Crown Group apartement in Sydney Australia.